Preparation and Low Temperature Short-term Storage for Synthetic Seeds of Caladium bicolor - Mehpara MAQSOOD; Abdul MUJIB; Mir KHUSRAU (Notulae Scientia Biologicae, 2015)
An efficient somatic embryo encapsulation and in vitro plant regeneration technique were established with Caladium bicolor, an important ornamental plant.Tuber derived embryogenic callus (95.50%) was obtained on Murashige and Skoog (MS) medium amended with 0.5 mg L-1 α-Naphthalene acetic acid (NAA) + 0.5 mg L-1 6-Benzyladenine (BA). The embryogenic callus later differentiated into somatic embryos in the same plant growth regulators (PGRs) added medium (NAA and BA). The induced embryos matured and developed into plantlets in NAA and BA added media; maximum plantlets development was observed at 1.0 mg L-1 NAA + 1.0 mg L-1 BA supplemented medium. Synthetic seeds were produced by encapsulating embryos in gel containing 3.0% sucrose + 3.0% sodium alginate and 100 mM of calcium chloride.The highest synthetic seed germination (97.6%) was observed on medium supplemented with 1.0 mg L-1 NAA + 1.0 mg L-1 BA. The synthetic seeds were kept at low temperatures for storage; the encapsulated beads were viable and demonstrated good germination even after 12 weeks of storage at 4 °C. The plantlet recovery frequency was however declined with time. The synthetic seed derived plantlets were morphologically similar to the mother plant.